2018
DOI: 10.2147/ndt.s152252
|View full text |Cite
|
Sign up to set email alerts
|

Long-term quality of life in cervical dystonia after treatment with abobotulinum toxin A: a 2-year prospective study

Abstract: BackgroundThe short-term quality of life (QoL) in cervical dystonia (CD) after treating with abobotulinum toxin A (Abo-BTX A) and neubotulinum toxin A (Neu-BTX A) have been studied in Thai CD patients. However; the long-term study has not been published.ObjectiveThe aim of the present study was to determine long-term improvement of the health-related quality of life (HRQoL) after eight injections of Abo-BTX A over 2 years in CD patients.Patients and methodsA 2-year prospective study on the QoL of CD patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
1
8
0
1
Order By: Relevance
“…The present patients showed reduced QOL, based on their OHIP-49 and SF-36 scores. Zurowsky et al [27] as well as others have confirmed that psychiatric illnesses have a major impact on QOL of patients with dystonia [34][35][36]. In our study, the dystonia patients consistently demonstrated lower QOL as compared to the healthy controls.…”
Section: Discussionsupporting
confidence: 76%
“…The present patients showed reduced QOL, based on their OHIP-49 and SF-36 scores. Zurowsky et al [27] as well as others have confirmed that psychiatric illnesses have a major impact on QOL of patients with dystonia [34][35][36]. In our study, the dystonia patients consistently demonstrated lower QOL as compared to the healthy controls.…”
Section: Discussionsupporting
confidence: 76%
“…However, this study used a large cohort, followed prospectively, and used a longer period of follow-up than that the majority of studies reported. This study was performed in Thailand in the Thai language, but all the PROs used have been previously validated in Thai [28][29][30][31]. Finally, this was an observational study using usual care rather than an intervention; the comparability of generic vs. SLE-specific HRQoL instruments needs to be confirmed in the setting of an interventional trial with an effective agent.…”
Section: Discussionmentioning
confidence: 99%
“…SLEQOL was developed in Singapore and incorporates questions suitable for oriental cultures [7]. Both SLE-QOL and SF36 surveys have been translated into Thai, validated [28,29], and used in many clinical studies in Thailand [30,31].…”
Section: Methodsmentioning
confidence: 99%
“…No entanto, a literatura ainda carece de consenso sobre os métodos utilizados para avaliar e monitorar continuamente esses pacientes, devido aos diferentes resultados obtidos de acordo com os instrumentos utilizados. (KONGSAENGDAO & MANEETON, 2018).…”
Section: Discussionunclassified